Transcription factor c‐Rel mediates communication between commensal bacteria and mucosal lymphocytes. Issue 5 (8th October 2021) - Luu, Maik; Binder, Kai; Hartmann, Sabrina; Kespohl, Meike; Bazant, Jasmin; Romero, Rossana; Schütz, Burkhard; Steinhoff, Ulrich; Visekruna, Alexander
Abstract: The NF‐κB transcription factor c‐Rel plays a crucial role in promoting and regulating immune responses and inflammation. However, the function of c‐Rel in modulating the mucosal immune system is poorly understood. T follicular helper (Tfh) cells and IgA production in gut‐associated lymphoid tissues (GALT) such as Peyer's patches (PPs) are important for maintaining the intestinal homeostasis. Here, c‐Rel was identified as an essential factor regulating intestinal IgA generation and function of Tfh cells. Genetic deletion of c‐Rel resulted in the aberrant formation of germinal centers (GCs) in PPs, significantly reduced IgA generation and defective Tfh cell differentiation. Supporting these findings, the Ag‐specific IgA response to Citrobacter rodentium was strongly impaired in c‐Rel‐deficient mice. Interestingly, an excessive expansion of segmented filamentous bacteria (SFB) was observed in the small intestine of animals lacking c‐Rel. Yet, the production of IL‐17A, IgA, and IL‐21, which are induced by SFB, was impaired due to the lack of transcriptional control by c‐Rel. Collectively, the transcriptional activity of c‐Rel regulates Tfh cell function and IgA production in the gut, thus preserving the intestinal homeostasis. Graphical Abstract: The transcription factor c‐Rel regulates intestinal homeostasis and protects against pathogen colonization; c‐Rel‐deficient mice display defective IgA production in the intestine.